Técnicas de restauração ecológica em nascentes e matas ciliares, Itaara, RS - Giacomini, Idiane Fátima (2016)
The present work had the purpose to evaluate the real potential of techniques in actions of ecological restoration in springs areas and riparian, searching to evaluate the dynamics of natural restoration in sixs springs under many different restorative treatment, in the city of Itaara, Meriodional Plateau of Rio Grande do Sul state.Were two through the achievement of floristic research of regenerating extract, between the years of 2014 and 2015, evaluated through of phytosociological parameters, diametric distribution, analisys of relation between springs with the species by DCA (rectified correspondence review) and indexes of diversity and similarity. The work also searched to evaluate the early behavior of six native forest species, introduced by direct sowing in a patch of riparian, where the species Schinus terebentifolius Raddi, Psidium cattleianum Sabine, Eugenia uniflora L., Cupania vernalis Cambess., Prunus myrtifolia L.(Urb.), Zanthoxylum rhoifolium Lam, was sown, evaluating the parameters, germination percentage, survival rate, and relative grown rate (TCR(%)). For the dynamics of the ecosystem structure of springs study, the results show of the natural regeneration comes to expanding in all springs, once the number of subjects and species gradually increased during the monitoring, proving of that areas have a little of resilience. . Is observed of the regenerative potential is centered in near remaining forest in each area of springs. For isdirect seeding,E. uniflora andC. vernalis, presented results for the germination, survival and development field. The rest os species didn’t have results for germination. The results reflects the need for attention to the lotof seeds and soil conditionsand management. That concludes of the techniques of simple isolation has the potential for ecological restoration through natural regeneration, provided that there is resilience. Direct seeding requires further experimental efforts to be validated for the study region. It is recommended of that strategies in the management for the preservation of riparian and springs are seen in a landscape context, taking into consideration not only the ecological aspects, but the economics and social too.